The Effect of Motivation and Work Discipline on Performance - Sharah Rizqiyyah; Badia Perizade; Zunaidah Zunaidah; Agustina Hanafi (International Journal of Social Service and Research, 2022)
This research aims to determine whether Motivation and Work Discipline affect Employee Performance at PT. Dizamatra Powerindo. This research uses primary data by distributing questionnaires to all employees. The total population used is 169 respondents where the entire population is samples. The analysis technique used is multiple linear regression analysis. The results obtained are that Motivation has a positive and significant effect on the performance of Employees of PT. Dizamatra Powerindo and Work Discipline have a positive and significant effect on the Performance of PT. Dizamatra Powerindo. Suggestions that can be given from this research is that Motivation at PT. Dizamatra Powerindo needs to be improved and for Work Discipline at PT. Dizamatra Powerindo leaders are expected to pay more attention to the dimensions of punctuality, then to improve the Performance of PT. Dizamatra Powerindo must be able to understand what motivation needs to be given to Employees to improve the Performance of the Employees.